Moving beyond content knowledge: Examining the impacts of a culturally responsive microbiology curriculum - Vasquez, Stacy (Frontiers in Education, 2022)
This paper describes the application of James A. Banks’ Levels of Integration of Multicultural Content to develop a culturally responsive curricular framework for a traditional 16-week microbiology course to determine its impact on classroom discourse. The study sought to qualitatively examine how the integration of multicultural content into a traditional microbiology course would, 1) change students’ impression of science and its relevance to their lived experiences, 2) impact students’ interest and perceived academic performance as it relates to retention of information, and 3) shape students’ understanding of sociopolitical issues. The multicultural curricular framework is summarized with a specific example described in detail. Qualitative data collected from two semesters of assignment prompts, classroom discussions, and end of semester focus groups are presented and discussed. Based on the results of the examined qualitative data, the multicultural curricular framework helped students better recognize the relevance of microbiology in relation to their lived experiences, increased their interest in science, improved their perceived academic performance, and increased their understanding of sociopolitical issues related to microbiology. Challenges and implications regarding integration of multicultural content into traditional microbiology courses are also discussed.